Attitude and knowledge for menopause management among health professionals in mainland China. (1st November 2020) - Lin, L.; Feng, P.; Yu, Q.
Abstract: Objective: This study aims to understand the attitude of health-care professionals (HPs) in mainland China toward menopause management (MM) as well as the knowledge they have received regarding MM during training. Methods: An anonymous survey recruited 3709 medical workers nationwide (including physicians, orthopedists, obstetricians and gynecologists, and general practitioners) through online surveys and on-site interviews at professional meetings. Results: Of the 3709 questionnaires completed, 3426 questionnaires met the inclusion criteria. Of the participants, 1532 HPs had not received menopause management training (MMT) in nearly 1 year. Among the residents and physician assistants, 103 reported they were not familiar with MM. Satisfyingly, 98.3% of HPs considered it very important or essential to accept MM. Although most interviewees replied some correct menopausal knowledge, nearly half of them could not correctly identify the contraindications for menopause hormone therapy (MHT). Additionally, 73.1% of HPs would advise patients with premature ovarian insufficiency to receive hormone replacement therapy at least until the average age of menopause. Conclusion: This survey indicated that HPs have some knowledge regarding MM, but a gap remains to master the basic theory of MHT. In order to manage the growing menopausal population in China, creating more in-depth educational MMT programs for HPs is necessary.